Evaluación de la contaminación acústica en la avenida Arízaga y la repercusión que provoca en los habitantes del sitio de influencia - Marín Toro, Cristhian Andrés (2015)
Noise pollution is an important environmental factor in every country on the planet. Human activity generates noise therefore, the higher noise levels occur where such activity is often concentrated. Today's society, using technological means at its disposal, has achieved many advances that have resulted in a definite improvement in the material standard of living, but at the same time, the increasing presence of noise has become inconvenient difficult to circumvent. New cities have tall buildings where the consequent overcrowding population derives greater social interference. Moreover, in these buildings thin walls and ceilings, an abundance of services and appliances as well as the inevitable result of human activity are frequent discomfort and conflict.